Peer Effects in Corporate Governance Practices: Evidence from Universal Demand Laws. (24th March 2021) - Foroughi, Pouyan; Marcus, Alan J; Nguyen, Vinh; Tehranian, Hassan
Abstract: Firms in the same networks tend to have similar corporate governance practices. However, disentangling peer effects, where governance practices propagate from one firm to another, from selection effects, where firms with similar preferences self-select into linked groups, is difficult to do. Studying board-interlocked firms, we utilize the staggered adoption of universal demand laws across states to identify and estimate causal peer effects in governance policies. We find support for the existence of peer effects in the adoption of antitakeover provisions. The impact of universal demand laws on the governance experience of interlocking directors likely explains these effects.